(untitled) (The Pakistan Development Review, 2012)
This paper explores the determinants of market diversification by export-oriented manufacturing firms using the logistic regression framework. The results show that firm level characteristics including age of the enterprise, managerial expertise, type of ownership, and size of the enterprise play a key role in determining the probability of market diversification by firms. These findings highlight the salience of firm level capacities in achieving export diversification in Pakistan. JEL Classification: F14, L25 Keywords: Exports, Firms, Market Diversification, Manufacturing